An expositional note on the transversality condition in continuous time dynamic economic models - Bianconi, Marcelo (Estudios Económicos de El Colegio de México, 1991)
This is an expositional note on the transversality condition in continuous time dynamic economic models. We illustrate the basic issues, using the neoclassical one-sector optimal growth asset pricing model. In this class of models, the transversality condition is the natural link tying the present to the distant future.